Literature Review: The Effect of Counseling on Knowledge of Reproductive Health of Prospective Bride and Grooms in Indonesia - Akhmadi Abbas; Silvia Ayu Amilia (Miracle Journal of Public Health, 2022)
Reproductive health in Indonesia is a problem that needs attention. Indonesia is a country with the second highest number of young marriages in ASEAN. In order to achieve a happy home life, the bride and groom (catin) need to follow guidance. This study aims to find out various counseling methods that are effective for increasing the knowledge of prospective brides (catin) in Indonesia. This research is a literature review study that reviews various research journals. Data obtained from secondary data taken from 7 previous research journals. The results showed that of the 7 journals there were similarities, namely that there was a significant influence on catin knowledge by holding reproductive health counseling.